2019
DOI: 10.1007/s11368-019-02245-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lead and beryllium sorption to exposed stream channel sediment under varying freshwater channel conditions

Abstract: and many others. I also want to again thank my committee members and my anonymous reviewers for their insightful and constructive comments on initial drafts of this thesis. Without them, this work would not be what it is today.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 96 publications
(166 reference statements)
0
4
0
Order By: Relevance
“…Different physicochemical factors influencing the distribution and desorption of Be were reported previously. ,, Edmunds and Islam et al reported that soil organic matters and oxyhydroxide of metals are important factors controlling Be distribution and transport. Moreover, Pawlowski and Karwan reported that the mobility of Be increased with the increase in DOC, and Taylor et al reported that Be-humate/fulvate complexes are often unstable and can be mobile in the environment, which may also be applied in this study, resulted in strong correlation ( R 2 = 0.926) between DOC and amount of Be in the leachate.…”
Section: Resultsmentioning
confidence: 73%
“…Different physicochemical factors influencing the distribution and desorption of Be were reported previously. ,, Edmunds and Islam et al reported that soil organic matters and oxyhydroxide of metals are important factors controlling Be distribution and transport. Moreover, Pawlowski and Karwan reported that the mobility of Be increased with the increase in DOC, and Taylor et al reported that Be-humate/fulvate complexes are often unstable and can be mobile in the environment, which may also be applied in this study, resulted in strong correlation ( R 2 = 0.926) between DOC and amount of Be in the leachate.…”
Section: Resultsmentioning
confidence: 73%
“…The authors use batch experiments with in-stream sediment deposits from two systems and varying solutions to replicate both background and elevated levels of iron oxide along with different dissolved organic carbon and sediment solution ratios. Pawlowski and Karwan (2019) found that the sorption of Pb and Be increased over time for all substrates and treatments. These authors demonstrated that sediment mineralogy, organic matter, and biogeochemical cycling processes may all affect the mobilization or retention of Pb and Be, potentially impacting their conservative behavior and thus their utility in sediment source fingerprinting research.…”
Section: Sediment Source Fingerprinting In the Critical Zonementioning
confidence: 87%
“…These authors demonstrated that sediment mineralogy, organic matter, and biogeochemical cycling processes may all affect the mobilization or retention of Pb and Be, potentially impacting their conservative behavior and thus their utility in sediment source fingerprinting research. Pawlowski and Karwan (2019) highlight that there may be a significant export of both 210 Pb xs and 7 Be in the solution phase along with other cations that may be exposed to the redox chemistry of a variety of oxides and hydroxides. These authors clearly illustrate how a variety of processes influence the development of fingerprint signals, and that it is important to strive to understand how these processes may affect sediment source fingerprints and source apportionment modeling.…”
Section: Sediment Source Fingerprinting In the Critical Zonementioning
confidence: 98%
See 1 more Smart Citation